2005
DOI: 10.1136/hrt.2005.069666
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structural and functional abnormalities in end stage renal disease patients with elevated cardiac troponin T

Abstract: Patients with ESRD with raised cTnT concentrations have increased mortality. Raised concentrations are strongly associated with diabetes, LV dilatation, and impaired LV systolic and diastolic function, but not with severe coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 34 publications
4
67
0
Order By: Relevance
“…[57,58] Assessment of diastolic function by echocardiography has shown a high incidence of abnormalities in dialysis and nondialysis CKD patients. [59,60] Similar to our study, some investigators have found abnormalities in tissue Doppler velocity in virtually all patients with CKD, suggesting a degree of subclinical myocardial disease in all such patients. [61] In the CRIC study (stage 2-4 CKD), diastolic function was abnormal in 71% of patients.…”
Section: Discussionsupporting
confidence: 89%
“…[57,58] Assessment of diastolic function by echocardiography has shown a high incidence of abnormalities in dialysis and nondialysis CKD patients. [59,60] Similar to our study, some investigators have found abnormalities in tissue Doppler velocity in virtually all patients with CKD, suggesting a degree of subclinical myocardial disease in all such patients. [61] In the CRIC study (stage 2-4 CKD), diastolic function was abnormal in 71% of patients.…”
Section: Discussionsupporting
confidence: 89%
“…In the nondialysis population, GLS is proved as a more reliable and sensitive parameter for representing LV systolic function in patients with cardiomyopathies, advanced-stage CKD, or HF with preserved LVEF (11,12,(27)(28)(29)(30). Less negative GLS is also proved as a powerful predictor of all-cause mortality in the general population (9), and is reported to be useful in the preclinical diagnosis of a number of other cardiomyopathies, including diabetes, hypertrophic cardiomyopathy, and amyloidosis (28)(29)(30). In these cardiomyopathies, only GLS precedes any clinical evidence of overt systolic dysfunction, suggesting that abnormal GLS may represent an early stage of abnormal LV geometry and function.…”
Section: Discussionmentioning
confidence: 99%
“…Although LV hypertrophy (LVH) and reduced LVEF are recognized as prognostic predictors in dialysis patients, most ESRD patients have LVH and preserved LVEF (ejection fraction $50%) (1,9,10). Therefore, a more promising method to evaluate cardiac functions is critical.…”
Section: Introductionmentioning
confidence: 99%
“…This causes progressive difficulty in troponin interpretation for a growing number of 'positive' individuals and increases the risk of misinterpretation (Table 1). [24][25][26] It may be argued this is irrelevant, as any troponin rise no matter what the underlying cause is significant and therefore worthwhile detecting. While this is true, the value of such a diagnosis and allocation of resources in doing so may be limited if the risk cannot be modified as a result e.g.…”
Section: Troponinmentioning
confidence: 99%
“…25 Troponin elevation in chronic renal failure patients is associated with evidence of diffuse myocardial injury. 26,27 The current generation of troponin assays is able to measure troponin levels in healthy normal individuals. It has been shown that the presence of an elevated troponin above the reference interval, currently defined as the 99th percentile, is associated with other cardiac risk factors 28 and with an increased risk of cardiac events such as MI 29,30 or risk of development of heart failure.…”
Section: Po Collinsonmentioning
confidence: 99%